Biological Membrane-Penetrating Peptides: Computational Prediction and Applications - de Oliveira, Ewerton Cristhian Lima; da Costa, Kauê Santana; Taube, Paulo Sérgio; Lima, Anderson H.; Junior, Claudomiro de Souza de Sales (Frontiers in Cellular and Infection Microbiology, 2022)
The computational prediction of penetration of peptides into the biological membranes has been developed aiming at different pharmaceutical and biotechnological applications and these analyses have gained continually attention of academia and industry due to their high throughput and low-cost screening of large libraries and the elucidation of the molecular mechanism of penetration. Structural, physicochemical, and sequence information of peptides, as well as atomistic biophysical models, have been explored in computer-assisted discovery strategies to classify and identify new structures with proper pharmacokinetics properties regarding their penetration into the biomembranes Computational strategies to predict the permeability into biomembranes include cheminformatics filters, molecular dynamics simulations, artificial intelligence algorithms, and statistical models and the choice of the most adequate method depends on the purposes of the computational investigation. Here, we exhibit and discuss some principles and applications of these computational methods widely used to predict the permeability of peptides into biomembranes, exhibiting some pharmaceutical and biotechnological applications of these structures.